Tata Kelola Perusahaan, Risiko Keuangan, dan Kinerja Perbankan di Indonesia - Margarita Ekadjaja, Agustin Ekadjaja, (Jurnal Ekonomi, 2020)
The balance of shareholders and stakeholders in managing the company is in line with the principles of Good Corporate Governance (GCG). Companies sometimes require additional external funds to develop their business. Fulfillment of external funding needs can be obtained from banking and non-banking financial institutions. The study population was banking companies for the period 2011 - 2018 using double linear regression as a data analysis tool. The results of the study found that banking corporate governance and financial risk have implications for banking performance.The results found that banking corporate governance and financial risk have implications for banking performance. The GCG variables, Net Interest Margin (NIM), and Loan Deposit Ratio (LDR) have a unidirectional relationship with banking performance. The variables of Non Performing Loan (NPL) and Expense to Operating Income (ETOI) have an opposite relationship, meaning that banks must reduce non-performing loans and operating costs to improve their bank performance.